The clearing of euro OTC derivatives post Brexit: Why a uniform regulation and supervision of CCPs is essential for European financial stability - Volker Brühl (Goethe University Frankfurt, Center for Financial Studies (CFS), 2018)
With a notional amount outstanding of more than USD 500 trillion, the market for OTC derivatives is of vital importance for global financial stability. A growing proportion of these contracts are cleared via central counterparties (CCPs), which means that CCPs are gaining in importance as critical financial market infrastructures. At the same time, there is growing concern that a new "too big to fail" problem could arise, as the CCP industry is highly concentrated due to economies of scale. From a European perspective, it should be noted that the clearing of euro-denominated OTC derivatives mainly takes place in London, hence outside the EU in the foreseeable future. For some time there has been a controversial discussion as to whether this can remain the case post Brexit. CCPs, which clear a significant proportion of euro OTC derivatives and are systemically relevant from an EU perspective, should be subject to direct supervision by EU authorities and should be established in the EU. This would represent an important building block for a future Capital Markets Union in Europe, as regulatory or supervisory arbitrage in favour of systemically important third-country CCPs could be prevented. In addition, if a systemically relevant CCP handling a considerable portion of the euro OTC derivatives business were to run into serious difficulties, this may impact ECB monetary policy. This applies both to demand for central bank money and to the transmission of monetary policy measures, which can be significantly impaired, particularly in the event that the repo market or payment systems are disrupted. It is therefore essential for the ECB to be closely involved in the supervision of CCPs. Against this background, the draft amendment of EMIR (European Market Infrastructure Regulation) presented on 13 June 2017 is a step in the right direction. In addition, there is an urgent need to introduce a recovery and resolution mechanism for CCPs in the EU to complement the existing single resolution mechanism (SRM) for banks in the eurozone. Only then can the diverse interdependencies between banks and CCPs be adequately taken into account in the recovery and resolution programmes required in a financial crisis.
urn:nbn:de:hebis:30:3-437425
Keywords: G20; G21; 330